Age-Specific Risk Factors and Post-Operative Complications in Patients with Intestinal Obstruction: Post-Operative Complications in Patients with Intestinal Obstruction - Shoukat, Hassan; Uttra, Muhammad Ismail Yar Khan; Malik, Muhammad Khan; Salam, Abdus; Shahid, Madeeha; Mahmood, Tariq; Muhammad, Shoaib (Pakistan Journal of Health Sciences, 2025)
Intestinal obstruction is among the most prevalent surgical challenges, which impacts millions of individuals and contributes significantly to morbidity and mortality. Objectives: To investigate the age-specific causes and post-operative complications in patients with intestinal obstruction. Methods: All patients who were clinically diagnosed with intestinal obstruction and subsequently underwent surgical intervention were enrolled in this prospective study. Participants were categorized into four age groups. Patients found to have peritonitis without evidence of obstruction during laparotomy were excluded. Operative and histopathological findings were documented, and the data were summarized using frequencies and percentages. Results: The study included 305 patients, 146 males (47.9%) and 159 females (52.1%). The most common causes of intestinal obstruction in group A were tuberculosis (n=32, 35.2%), and adhesions (n=22, 33.3%) were a common etiological factor in group B; malignancies predominated in the elderly. The incidence of post-operative complications was 7.21%. Conclusions: It was concluded that the etiology of intestinal obstruction in adults varies significantly with age, necessitating age-specific diagnostic and therapeutic approaches.